Konsep Iman, Akal dan Wahyu dalam Al-Qur’an - Muh. Dahlan, MA Thalib (IAIN PAREPARE, 2022)
Abstract The concepts of Faith, reason and revelation are nuanced with reflection, all of which are encouraged and developed in order to understand phenomena both materially and non-materially. In a neutral sense, the Qur'an speaks of faith in two different, though not contradictory, essences, namely faith is simply belief and belief as well as proof. Furthermore, Aqal or fakara and faqiha, as well as nadzara or bashara and aspects of dzakara as human reflection power, are all human essences with which the mandate of the caliphate can be carried out by humans. While revelation does not only come from God, but also other than God, and is not only addressed to the Prophet or Apostle, but also to others. In a specific sense, revelation is the Qur'an not only because the entire content of revelation is contained in the Qur'an, but also the Qur'an is clearly stated as revelation. The two meanings of revelation have similarities that revelation is an encouragement to do something whose presence occurs in secret. Keywords: Faith, Reason, Revelation and the Qur'an